Filantropía, rehabilitación y terapia ocupacional : Buenos Aires y Río de Janeiro (1943-1960) - Testa, Daniela Edelvis (2018)
El artículo examina dos asociaciones de carácter filantrópico consideradas "pioneras" en la rehabilitación de discapacidades motrices: la Asociación para la Lucha contra la Parálisis Infantil (ALPI), de la ciudad de Buenos Aires, y la Asociación Brasilera de Beneficencia para la Rehabilitación de Rio de Janeiro (ABBR), entre 1943 y 1960. Se analiza la circulación de ideas, los modelos asistenciales y de gestión adoptados y la relación de estas entidades con la formalización de los primeros cursos regulares de nivel superior de terapia ocupacional
The article examines two philanthropic associations considered "pioneers" in the rehabilitation of motor disabilities: Asociación para la Lucha contra la Parálisis Infantil (Association for the Fight against Child Paralysis), of Buenos Aires city (ALPI) and Associação Brasileira Beneficente de Reabilitação of Rio de Janeiro city (ABBR) (Brazilian Association of Charities for the Rehabilitation of Rio de Janeiro) (ABBR), between 1943 and 1960. The paper analyzes the circulation of ideas, the care and management models adopted and the relationship of these entities with the formalization of the first regular courses of higher level of occupational therapy
Keywords: Filantropía; Rehabilitación; Terapia ocupacional; Philantrophy; Rehabilitation; Occupational therapy